Factors associated with progression of arterial stiffness in ischemic stroke survivors: the Norwegian Stroke in the Young Study - Rune Krogh Eilertsen; Helga Midtbø; Rasmus Bach Sindre; Ulrike Waje-Andreassen; Eva Gerdts (Blood Pressure)
Background Progressive arterial stiffening may increase the risk of recurrent cardiovascular events in ischemic stroke survivors. Information about factors associated with progressive arterial stiffening during the follow-up of young patients with ischemic stroke is lacking.Methods Arterial stiffness by carotid-femoral pulse wave velocity (cf-PWV) and ambulatory 24-hour blood pressure (24hBP) were assessed in 81 women and 190 men ≤60 years of age included in the Norwegian Stroke in the Young (NOR-SYS) study 3 months and 5.5 years after the incident ischemic stroke, representing baseline and follow-up. Covariables of change in cf-PWV were identified using linear regression analysis.Results At baseline, women had less prevalent hypertension (53% vs. 69%, p < 0.05), and lower clinic and 24hBP than men, whereas age, obesity, and prevalence of smoking and antihypertensive drug treatment did not differ. During follow-up, systolic 24hBP remained unchanged, while diastolic 24hBP fell significantly (p < 0.01). Cf-PWV was lower in women both at baseline (7.3 m/s vs. 8.1 m/s) and at follow-up (7.3 m/s vs. 8.0 m/s, both p < 0.001), but the average change during follow-up did not differ between genders. In linear regression analysis, an increase in cf-PWV at the 5-year follow-up was associated with the presence of hypertension and lower cf-PWV at baseline, and higher systolic 24hBP and lack of use of antihypertensive treatment at follow-up (all p < 0.05).Conclusion In ischemic stroke survivors participating in the NOR-SYS study, the 5-year increase in cf-PWV did not differ between genders and was associated with higher systolic 24hBP and lack of antihypertensive treatment.